Sebaceous gland carcinoma of the eyelid: case report (1990)
This paper reports a case of sebaceous adenocarcinoma of the meibomian gland in a 69-yearold man. The tumour was excised and histopathological examination revealed the characteristic features of sebaceous adenocarcinoma should then consist of wide excision, with preparation of frozen sections during the operation to ensure tumour-free borders.